Positive association between weight-adjusted-waist index and hyperuricemia in patients with hypertension: The China H-type hypertension registry study - Zhao, Peixu; Shi, Weidong; Shi, Yumeng; Xiong, Yurong; Ding, Congcong; Song, Xiaoli; Qiu, Guosheng; Li, Junpei; Zhou, Wei; Yu, Chao; Wang, Tao; Zhu, Lingjuan; et al. (Frontiers in Endocrinology, 2022)
Background and Aims: The relationship between the new obesity index weight adjusted waist index and hyperuricemia is unclear. We aimed to explore the association of weight-adjusted-waist index (WWI) and hyperuricemia among hypertensive population. Methods: A total of 14078 hypertension participants with complete data were included in our study. WWI was calculated by waist circumference (WC) divided by the square root of weight. Specifically, men with 420 μmol/L and women with 360 μmol/L were considered hyperuricemia. Results: The prevalence of hyperuricemia was 61.1% in men and 51.4% in women. On the whole, multivariate logistic regression analyses found that there was a linear positive correlation of WWI with hyperuricemia both in men (OR: 1.36; 95% CI: 1.24, 1.49) and women (OR: 1.37; 95% CI: 1.27, 1.47). Subgroup analysis found that the relationship between WWI and hyperuricemia was stable in stratified subgroups (all P-interaction >0.05). Conclusion: WWI showed positively association with the hyperuricemia among hypertension patients.